Pesquisa de satisfação dos alunos em relação ao curso de Estradas no IFAL - Campus Maceió - Lima, Maria Eduarda dos Santos e Silva (2023)
The technical course in Roads aims to create professionals capable of assisting in road works, from planning to project implementation. At IFAL, the course was inaugurated in 1962 and has since been part of the list of integrated technical courses offered by the institute. Through data collection and research conducted, it has been proven that the course has gone through various changes throughout its history in the institution, from a name change to its existence in a certain period. However, the main objective of the work is to analyze the satisfaction of road students at IFAL-Campus Maceió at present and point out possible reasons for their discontentment or approval of the course, taking into consideration historical information about the course and then determine if the responses correspond to the current reality. This work also analyzed testimonies from former students, teachers, and ex-teachers, in addition to verifying the responses given by current students, and also telling a bit about the course's evolution throughout its history in the institution, exploring relevant problems, achievements, and other pertinent issues. Finally, a comparison was made between some current and old IFAL documents regarding the Roads course, which brought relevant data to understand many questions that arose during the work, as well as to enrich the research. Ultimately, a comparison was made between some documents related to the course and its current reality in the institution, where it is possible to verify that despite the course theoretically meeting the requirements to exist and function, it presents serious problems in ensuring the necessary support and resources for its students, ultimately generating great dissatisfaction among most students upon entering the course, contributing to a not-so-good experience in taking it.